Table tennis as method of development of co-ordinating capabilities of collegians - Коломійцева [Kolomiytseva O.] Ольга Едуардівна; Радченко [Radchenko Ya.] Я. (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> In the article the presented results of initial researches of level of development of coordinating capabilities and separate properties of attention of collegians which chose sectional employments table tennis as a form of organization of physical education. In researches 80 students took part 15-16 years (40 youths and 40 girls). The got results, in most cases, testify to the middle level of development of coordinating capabilities and properties of attention of teenagers. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>